KEPEMIMPINAN CAMAT DAN KINERJA KECAMATAN SAIL KOTA PEKANBARU TAHUN 2015-2016 - Jufriadi "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by Law Number 23 Year 2014 Article 225 Paragraph (1) which explains about the duty of subdistrict head. Sail Sub-district is a district that has the last rank in Pekanbaru City based on evaluation result of sub-district performance performed by Kecamatan Evaluation Performance evaluation team (EKK). This is the result of the evaluation of the worst evaluation in two consecutive years ie for the year 2015 and 2016. Sail District which has the same assessment indicators with other sub-districts located in Pekanbaru City but in its application is still very far from what is expected, whereas every sub-district in Pekanbaru City has the same reference in applying each policy based on the regulations that apply either the Law or the local regulation governing the running of a government system in a region, especially Sail District, which became the focus in this research. Based on the background of the problem, this study aims to describe the leadership of the Sail sub-district in the performance of Sail District Pekanbaru City in 2015-2016. Research Methods used in the writing of this thesis is Qualitative. Data type in this research is primary data and secondary data. Data collection techniques in this study are interviews, observation and documentation. Data analysis technique used is descriptive qualitative.The results of this study indicate that the leadership of Sail Kota Pekanbaru sub-district 2015-2016 is influenced by leadership style such as motivation style, power style (autocratic, participative, freestyle) and style of supervision. Furthermore, other factors that influence the leadership of Sail Sub-district in improving the performance in Kecamatan Sail Then in terms of employee performance that most influence is individual factors, team factors and leadership factors.Keywords: Leadership Camat, Performance Employees